PEMBERIAN CAMPURAN TRICHOKOMPOS DENGAN ABU JANJANG KELAPA SAWIT DI MEDIUM SUBSOIL ULTISOL TERHADAP PERTUMBUHAN KELAPA SAWIT (Elaeis guineensis Jacq.) DI PEMBIBITAN UTAMA - Prayogi ' Hutomo; Sampoerno ' '; Fifi Puspita ' Puspita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research aimed effect of Trichocompost with oil palm bunch ash mix giving in ultisol subsoil medium on oil palm’s growth and to the effective dosage. The research was conducted fromJunetoSeptember 2015. The research was a factorial experiments using Completely Randomized Design (CRD),the factor consist of Trichocompost and oil palm bunch ash mixed (T) consisted of 5 levels, without Trichocompost and oil palm bunch ash giving (T0), 25 g/polybag Trichocompost and 16 g/polybag oil palm bunch ash (T1), 50 g/polybag Trichocompost and 20 g/polybag oil palm bunch ash (T2), 75 g/polybag Trichocompost and 24 g/polybag oil palm bunch ash (T3) and 100 g/polybag Trichocompost and 28 g/polybag oil palm bunch ash (T4). The result of the research showed that Trichocompost and oil palm bunch ash givingin ultisol subsoil medium has significantly affected on oil palm seedling’s growth in main nursery. The application of 100 g/polybag Trichocompost with 28g/polybag oil palm bunch ash was effective in increasing plant height, leaf number, steam diameter, root volume, crown root ratio and plant dry weight. Keyword: Trichocompost, oil palm bunch ash, ultisol subsoil, oil palm’s seedling